Komunikasi Pembangunan Dalam Mengedukasi Masyarakat Terhadap Program Pemberian Makanan Tambahan (PMT) Untuk Mencegah Stunting Di Kelurahan Sungai Baru Kec. Banjarmasin Tengah - Amelia Puspita; Devia Hetty Hernany; Farisa Salsabila; Trinita Netiska (Journal on Education, 2024)
This study aims to analyze the implementation of development communication in the Additional Food Program (PMT) in Sungai Baru Village as a community education effort to prevent stunting. The research employs a qualitative descriptive approach using observation, interviews, and documentation techniques. The findings show that socialization through counseling sessions at health posts and community meetings effectively increased the understanding of pregnant women and mothers of young children about the importance of balanced nutrition. Innovations such as the "Healthy Kitchen to Overcome Stunting" program, in collaboration with DPPKBPMP and PLKB, successfully provided practical training, nutritious food aid, and empowered the community with cooking skills and nutritional knowledge. However, the study also identified challenges such as low educational levels, limited human resources, and economic factors affecting PMT distribution and education. Fluctuations in the number of stunted children indicate the need for continuous intervention and regular evaluation to optimize the program. The study concludes that despite challenges, strong commitment and collaboration with various stakeholders are essential to ensuring the effectiveness and sustainability of the program in addressing stunting in Sungai Baru Village.